2009
DOI: 10.1590/s0103-90162009000500013
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal communities in native and in replanted Araucaria forest

Abstract: Araucaria angustifolia is an important Brazilian conifer, but it is endangered of extinction due to excessive logging. The objective of the present case study was to survey data on the diversity of AMF in Araucaria angustifolia forests, and to learn whether it is possible to discriminate between the AMF communities associated with natural, introduced, and impacted-byanthropogenic-action ecosystems. Three ecosystems representative of the Campos do Jordão (São Paulo State, Brazil) region were selected, as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
2
6
1
7
Order By: Relevance
“…The Acaulospora genus was the second most abundant AMF spore in the experiment (Table 2), corroborating with the fact that the Acaulospora AMF has been found in moderate acidy soils (pH lower than 6.2) [30] and very acidy forest soils [24]. The least abundant genus in this experiment belonged to the genus Gigaspora (Table 2).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The Acaulospora genus was the second most abundant AMF spore in the experiment (Table 2), corroborating with the fact that the Acaulospora AMF has been found in moderate acidy soils (pH lower than 6.2) [30] and very acidy forest soils [24]. The least abundant genus in this experiment belonged to the genus Gigaspora (Table 2).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies indicated that araucaria is capable of supporting AMF symbiosis with a greater number of different fungal species [11,[22][23][24][25] than that we found in this experiment. To date, araucaria AMF spore richness varied from 8 [23] to 13 [11] in forests of the State of Rio Grande do Sul and from 26 [24] to 58 [25] in forests of Sao Paulo. The variation in spore AMF richness has been frequently attributed to heterogeneity in soil habitat and to the variable capacity of AMF species to adapt to climate and soil in different regions [10,13].…”
Section: Discussioncontrasting
confidence: 46%
“…For the preservation of this forest, the presence of a high diversity of arbuscular mycorrhizal fungi (Moreira et al, 2009) and diazotrophic bacteria (Lammel et al, 2007), heterotrophic bacteria and archaebacteria (Maluche-Baretta, 2007;Bertini, 2010), and soil invertebrates (Merlim, 2005;Baretta et al, 2010) is fundamental. Conservation is therefore an urgent issue that must be addressed without delay, since the soil quality is fundamental, not only for food, timber, fiber, and fuel production, but also for the maintenance of biodiversity and environmental quality (Doran & Zeiss, 2000;Bastida et al, 2006;Kaschuk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their importance to plant productivity and sustainability of agricultural systems (Barea, 1991;Smith & Read, 1997), AMF are widely distributed through the most diverse forest ecosystems, as rain forest in southern Queensland-Australia (Gehring & Connell, 2006), Clintonia borealis roots from a boreal mixed forests in northwestern Québec (DeBellis & Widden 2006), hot-dry valley of Jinsha River, southwest China (Dandan and Zhiwei, 2007), forest with Araucaria angustifolia in Brazil (Moreira et al, 2007;Moreira et al 2009;Patreze et al, 2009), in the Atlantic Forest in Southeastern Brazil (Zangaro et al, 2007(Zangaro et al, , 2009, Hepatica nobilis Mill. site type spruce forest at central Estonia (Uibopuu et al, 2009), semievergreen tropical forest at southeast Mexico (Ramos-Zapata et al, 2011a), Podocarpus cunninghamii forests from New Zealand (Williams et al, 2011), young and old secondary forest in Western Brazilian Amazon (Stürmer & Siqueira, 2011), coastal dunes of Sisal, Mexico (Ramos-Zapata et al, 2011b) and floodplain islands as recently related at northeastern Italy (Harner et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The approach which has been conducted is the evaluation of soil quality by direct counts of spores extracted from soil (Carvalho et al, 2003;Moreira et al, 2009), through assessment of percentage of colonized roots (Moreira et al, 2007, Patreze et al, 2009, and estimation of length and biomass of hyphae in the soil using hyphal 32 P-labelling (Pearson & Jakobsen, 1993). According to Rosendahl (2008), quantitative studies of arbuscular mycorrhizal fungal communities based on the presence of spore numbers are complicated as some species produce few spores on the mycelium, whereas species such as G. intraradices, G. versiforme or G. fasciculatum produce hundreds of spores on the same hypha.…”
Section: Wwwintechopencommentioning
confidence: 99%